Intertrochanteric fractures treated by diaphyseal support arthroplasty with hook plate vs cerclage wires only: A retrospective cohort study. (December 2021) - Abboud, Ghadi; Maalouly, Joseph; Tawk, Antonios; Aouad, Dany; Ayoubi, Rami; Najm, Talal; El-Hajj, Gerard; El Rassi, George; Nehme, Alexandre
Abstract: Background: The treatment of unstable fractures of the intertrochanteric region of the hip in the elderly is controversial. Conventionally, internal fixation with intramedullary nail or a dynamic hip screw is the treatment of choice in intertrochanteric fractures. Nowadays, some authors encouraged the use hip arthroplasty for management of these fractures with good outcome. The aim of this study is to compare total hip arthroplasty with hook plate against total hip arthroplasty with cerclage cables in the management of unstable intertrochanteric fractures. Materials and methods: Out of 100 admitted patients to a central university hospital in Beirut between 2013 and 2019 with a diagnosis of unstable intertrochanteric fracture of the hip, only 64 (36 hook plate vs 28 cerclage) patients were selected. This is a retrospective study, patients were excluded if lost to follow up, or if follow up less than one year is available. The data were retrieved from inpatient and outpatient hospital files. Functional outcomes were assessed according to ambulatory capacity. The main clinical measures were early postoperative full weight bearing, postoperative complications, functional outcome and radiologic assessment done by a radiologist in addition to measuring the dysfunction via the Harris Hip Score. Results: The time to full weight bearing, the rate of postoperative complications, radiologic outcome and the functional outcomes were more satisfactory in the hook - plate group than in the cerclage - cable group. Conclusion: According to the results, total hip arthroplasty with hook plate is considered the preferred modality of treatment in mobile elderly patients above sixty-five years of age with an unstable intertrochanteric femoral fracture, despite being a bulky foreign material that can lead to trochanteric bursitis. Highlights: Unstable intertrochanteric fractures (AO classification, A22-A23) are associated with a high mortality rate in the 1 st postoperative year among the elderly population with traditional osteosynthesis failing to treat these fractures as it is associated with several complications such as excessive collapse, loss of fixation, malalignment, femoral head necrosis and cut-out of the lag screw. Based on more recent studies, many surgeons are suggesting that unstable intertrochanteric fractures can successfully be treated with total hip arthroplasty as a primary form of operative treatment as it allows earlier postoperative weight-bearing and reduces collapse at the fracture site. The fixation of the greater trochanter, which is of the utmost importance in those cases, can be achieved with the aid of hook plates and cerclage wires or cerclage wires alone. This 7-years (Beirut, 2013 - 2019), retrospective cohort study concluded that hook plate is more advantageous than cerclage cables alone for the treatment of unstable intertrochanteric fractures among the elderly population. Clear benefits of this management are early full - weight bearing; fewer complications, including pressure sores, pulmonary infection, and atelectasis; and early return to ADLs. While the hook plate is a better option for anatomic reconstruction and functionality, it is a bulky foreign material which may lead to trochanteric bursitis.